Resources against communalism and religious fundamentalism in India - Kapoor, Harsh; Safdar Hashmi Memorial Trust (New Delhi : SAHMAT, 1996)
A bibliography of some of the available material on communalism and religious fundamentalism in India.
Includes index.
Keywords: Communalism -- India -- Bibliography; Hindus -- India -- Bibliography; Muslims -- India -- Bibliography; India -- Ethnic relations -- Bibliography; 69-91